Assessing the Geological Environment Resilience Under Seawater Intrusion Hazards: A Case Study of the Coastal Area of Shenzhen City - Dong Su; Jinwei Zhou; Maolong Huang; Wenlong Han; Aiguo Li; Enzhi Wang; Xiangsheng Chen (Journal of Marine Science and Engineering)
Revealing geological environment resilience (GER) under seawater intrusion (SWI) hazards is a prerequisite for solving groundwater resource depletion, land salinization, and ecological degradation in coastal cities. This study applies the resilience design approach based on urban complex adaptive systems theory to understand the impact of SWI on the geological environment. Taking SWI as the research object, the GER evaluation method under SWI disaster was established by selecting five elastic indexes: disturbance intensity, geological environment vulnerability, stress resistance, recovery, and adaptability. This method is used to evaluate the GER level of the coastal areas of Shenzhen in recent years under the impact of SWI hazards. The study found that there is a negative correlation between the intensity of disturbance and precipitation amount. The vulnerability is greater the closer the distance to the coastline and the shallower the depth of bedrock burial. Resistance is composed of early warning ability and disaster prevention ability, and the result is 10.07, which belongs to the medium level. The recovery is 1.49, which is at a relatively high level, indicating a high capacity for restoration ability. The adaptability increased from 3.03 to 3.13, so that the area of seawater intrusion is becoming smaller. GER is affected by precipitation amount and depth of bedrock burial; the greater the precipitation and the shallower the bedrock burial, the lower the GER. Precipitation amount significantly impacts the SWI situation in the eastern coastal area of Shenzhen. In the central region, the impact of precipitation on GER is less significant. However, in the western region, the depth of bedrock burial primarily affects GER. Compared to completely weathered granite, Pleistocene fluvial plain sediments are more susceptible to SWI effects in freshwater environments. This study contributes to a deeper understanding of the impact of SWI on the geological environment in coastal areas, providing decision-makers with the necessary knowledge to develop targeted and effective governance and prevention strategies.